1994
DOI: 10.1152/jn.1994.71.5.1848
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive coordination of movement sequences: role of velocity and position information

Abstract: 1. Recent studies have shown that the CNS uses proprioceptive information to coordinate multijoint movement sequences; proprioceptive input related to the kinematics of one joint rotation in a movement sequence can be used to trigger a subsequent joint rotation. In this paper we adopt a broad definition of "proprioception," which includes all somatosensory information related to joint posture and kinematics. This paper addresses how the CNS uses proprioceptive information related to the velocity and position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(102 citation statements)
references
References 0 publications
5
93
0
4
Order By: Relevance
“…The reduced ability of old adults to reproduce a target velocity during fast movements (Fig. 3B), which are influenced the least by peripheral feedback (8), may suggest an impaired motor program (motor command and excitation of the motoneuron pool). A similar conclusion was reached in previous studies that used larger muscles and different tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced ability of old adults to reproduce a target velocity during fast movements (Fig. 3B), which are influenced the least by peripheral feedback (8), may suggest an impaired motor program (motor command and excitation of the motoneuron pool). A similar conclusion was reached in previous studies that used larger muscles and different tasks.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Tactile and proprioceptive information from the distractor was available to one hand before the signal was given to start the reach-to-grasp movement toward the target with the other hand. This procedure was followed because there is evidence suggesting that proprioceptive afferents play a significant role, along with cutaneous afferents, in the perception of hand conformation (Cordo, Carlton, Bevan, Carlton, & Kerr, 1994;Johnson, Yoshioka, & Vega-Bermudez, 2000). If proprioceptive and haptic information from the distractor is made available, then, in line with the findings of these authors, we would expect interference of this information on the kinematics of the hand reaching toward the target.…”
mentioning
confidence: 99%
“…Aschersleben (in press) found that the anticipatory constant errors seen in synchronization with external stimuli disappear with extensive practice, as long as KR is given. Cordo et al (1994) studied a task similar to that reported here, but one in which KR was given on every trial. They observed much smaller errors than those in our study, and these were not always anticipatory.…”
Section: Resultsmentioning
confidence: 99%
“…Cordo (1990) suggested that proprioceptive input related to the active rotation of a joint might be useful for triggering movement at another joint during movement sequences. On the basis of those assumptions, he ran a series of experiments in order to investigate whether the central nervous system (CNS) can use kinaesthetic input to coordinate multijoint movement sequences (Cordo, 1990;Cordo, Carlton, Bevan, Carlton, & Kerr, 1994;Corda & Flanders, 1989). In the Cordo et al experiment, the elbow was extended passively, and the subject opened the hand as the arm passed through a target zone.…”
Section: Response Effects In Movement Coordinationmentioning
confidence: 99%